Salary Disparity and Team Performance: An Empirical Analysis of the English Premier League - Alexander Traugutt; Jarid Morton (Journal of Applied Sports Management, 2024)
The English Premier League (EPL) is the top-tier English soccer system, becoming one of the most popular sports leagues in the world. One topic within the EPL that has garnered significant attention is player compensation and roster construction. Given the varied outputs of players and the spending power of each club, the question becomes whether a specific type of pay structure maximizes on-field performance. Thus, this study aimed to understand the effect of intra-team salary disparity on performance. Results indicated that while rosters tend to be organized in a more compressed manner, salary disparity was not a significant predictor of team success. Instead, a roster constructed around a greater number of impact players was found to be the most positive predictor of performance. The insights from this study have practical managerial and strategic planning implications in sports leagues seeking to optimize performance amidst intra-team salary disparities.
Keywords: English Premier League; organizational behavior; salary; economics